Regional Characteristics and Effects of Inward Fdi: the Case of Ukraine - Kokko, Ari; Kravtsova, Victoria (Organizations and Markets in Emerging Economies, 2012)
This paper contributes to the analysis of the impact of FDI on host countries by taking into account the regional dimension of spillover effects. Focusing on the case of Ukraine, we explore the effects of inward FDI on changes in productivity, technology, and efficiency in local firms. For the country as a whole, the results suggest that the presence of foreign-owned firms had a negative impact on productivity change in local firms during the period 1999-2003. However, there were notable differences between the effects in the western and eastern parts of the country: the overall findings were mainly driven by the development in western Ukraine, whereas inward FDI in eastern Ukraine did not seem to have any impact on local productivity growth and technical change. These results arguably reflect deep economic and institutional differences between the two parts of Ukraine, which have led to differences in the character of incoming FDI and differences in the ability of local firms to benefit from FDI. The conclusion is that the impact of FDI on the host economy may vary even at the sub-national level, depending on the specific local environment.
Keywords: FDI; regional spillover effect; Malmquist productivity index